Clinical evaluation of a multi-fixation campimeter for the detection of glaucomatous visual field loss. Issue 6 (June 1993) - Mutlukan, E; Damato, B E; Jay, J L
Abstract : The multi-fixation glaucoma screening chart, which uses the oculokinetic perimetry (OKP) technique, is a hand-held tangent screen with a central black test stimulus on a white background and a series of 26 numbered fixation targets arranged around the stimulus at various locations. When the numbers on the chart are read by the patient from 40 cm distance, the test stimulus passes through the relevant parts of the central visual field which are most vulnerable to glaucomatous damage. The test is positive (that is, abnormal) if at least one fixation number is associated with consistent disappearance of the stimulus. The OKP test was performed in 222 eyes of 126 glaucoma patients (aged 16-91 years) and 186 right eyes of 186 normal individuals (aged 19-86 years) using a 1.5 mm diameter stimulus. A further 144 eyes of 88 glaucoma patients (aged 60-85 years) and 31 right eyes of 31 normal individuals (aged 60-85 years) were tested with a 3 mm diameter stimulus. All eyes were also tested with conventional perimetry and the results of the conventional perimetry were categorised according to the Aulhorn-Karmeyer classification by four ophthalmologists without any knowledge of the OKP results. When the 1.5 mm stimulus was used, a true positive OKP result was obtained in 45% of eyes with relative scotomas, 81% of eyes with small absolute scotomas separate from the blind spot and 100% of eyes with more severe visual field defects.(ABSTRACT TRUNCATED AT 250 WORDS)